Consideration of Nursing Care Demand for Families in Disaster: A Literature Review - Hastoro Dwinantoaji; Mami Nojima (Alta Dharma Publisher, 2020)
This review aimed to examine the existing literature in English and Japanese on family needs during disaster. We identified the necessary care for families by focusing on nursing activities and needs among patients and their families in each phase of the disaster. The databases searched in this review were Academic Search Premier, Medline, CINAHL, and Igaku Chuo Zasshi. Three keywords—“disaster,” “family,” and “nursing”—were searched both separately and in combination in Japanese and English languages. Results showed various specific nursing activities and needs for families, community, staff (doctors, nurses, and care workers), and facilities (home-visit nursing office and hospital) in each disaster phase. In the pre-impact phase, prevention, protection, and preparedness were emphasized. During the impact phase, primarily securing place, assessing environment, and providing psychological first aid for survivors and families were emphasized. The post-impact phase focused on the recovery of all aspects of the disaster’s impact. In conclusion, the necessary care for families in each phase of disasters is to protect human life and security. Nurses should carry out disaster-response activities based on human life and security. In addition, nurses should focus on family members who have health concerns before the disaster and build the family support system.